Freedom's Prophet : Bishop Richard Allen, the AME Church, and the Black Founding Fathers. - Newman, Richard S. (NYU Press, 2008)
An Interview with the Author on the History News Network. A Founding Father with a Vision of Equality : Richard Newman's op-ed in The Philadelphia Inquirer. Author Spotlight in The Rochester Democrat and Chronicle. "Gold" Winner of the 2008 Foreword Magazine Book of the Year Award, Biography Category. Freedom's Prophet is a long-overdue biography of Richard Allen, founder of the first major African-American church and the leading black activist of the early American republic. A tireless minister, abolitionist, and reformer, Allen inaugurated some of the most important institutions in.